Women-centred design – New trajectories for medical design - Francesca Toso; Alessia Buffagni; Martina Frausin (Agathón)
The lack of attention to the specific needs of women in the design processes of health and wellness products has led to the proliferation of ineffective solutions and stereotypes that overlook the physiological, biological, behavioural, and socio-cultural characteristics of the female population. Through a critical review of international literature, this paper presents a selection of methodological approaches that place women ‘at the centre of design’. The selected case studies identify three possible design trajectories guided by: 1) biological and physiological matrices, 2) anatomical matrices, and 3) socio-cultural matrices. From this analysis, design principles emerge that guide strategies for developing appropriate and accessible technologies that can contribute to raising designers’ awareness and dismantling bias and stereotypes when integrated into the educational system.